Angry planet : decolonial fiction and the American third world - Stewart, Anne, 1981- (University of Minnesota Press, 2022)
"Many novels from the end of the millennium center around an Earth that acts, moves, shapes human affairs, and creates dramatic, nonanthropogenic change. Anne Stewart shows how this fiction brought Black and Indigenous thought into conversation, offering a fresh account of globalization in the 1990s-the era that first made connections among environmental crises and antiracist and decolonial struggles"--